Ionic Liquids Increase the Catalytic Efficiency of a Lipase lip1 from an Antarctic Thermophilic Bacterium - Blamey-Alegria, J (Springer Verlag, 2014)
Lipases catalyze the hydrolysis and synthesis of triglycerides and their reactions are widely used in industry. The use of ionic liquids has been explored in order to improve their catalytic properties. However, the effect of these compounds on kinetic parameters of lipases has been poorly understood. A study of the kinetic parameters of Lip1, the most thermostable lipase from the supernatant of the strain ID17, a thermophilic bacterium isolated from Deception Island, Antarctica, and a member of the genus Geobacillus is presented. Kinetic parameters of Lip1 were modulated by the use of ionic liquids BmimPF6 and BmimBF4. The maximum reaction rate of Lip1 was improved in the presence of both salts. The highest effect was observed when BmimPF6 was added in the reaction mix, resulting in a higher hydrolytic activity and in a modulation of the catalytic efficiency of the enzyme. However, the catalytic efficiency did not change in the presence of BmimBF4. The increase of the reaction rates of Lip1 promoted by these ionic liquids could be related to possible changes in the Lip1 structure. This effect was measured by quenching of tryptophan fluorescence of the enzyme, when it was incubated with each liquid salt. In conclusion, the hydrolytic activity of Lip1 is modulated by the ionic liquids BmimBF4 and BmimPF6, improving the reaction rate and the catalytic efficiency of this enzyme when BmimPF6 was used. This effect is probably due to changes in the structure of Lip1 induced by the presence of these ionic liquids, stimulating its catalytic activity. © 2014 AOCS.